2011
DOI: 10.1021/ic102194z
|View full text |Cite
|
Sign up to set email alerts
|

Group 4 Complexes of atert-Butylphosphine-Bridged Biphenolate Ligand

Abstract: The coordination chemistry of group 4 complexes supported by the tridentate, dianionic biphenolate phosphine ligand that carries a phosphorus-bound tert-butyl group, 2,2'-tert-butylphosphino-bis(4,6-di-tert-butylphenolate) ([(t)Bu-OPO](2-)), is described. Metathetical reactions of {[(t)Bu-OPO]Li(2)(DME)}(2) with 2 or 1 equiv of TiCl(4)(THF)(2) selectively produce [(t)Bu-OPO]TiCl(2)(THF) (1a) and Ti[(t)Bu-OPO](2) (2a), respectively. Protonolysis of Ti(O(i)Pr)(4) with 2 or 1 equiv of H(2)[(t)Bu-OPO] cleanly gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…12 etc. In the presence of one equiv of e-CL, the 27 Al chemical shift of 2b moves upfield to 129 ppm (Dv 1/2 = 11157 Hz), consistent with an increase in coordination number for a neutral organo-aluminum complex. 75,80 The 1 H NMR spectrum of the same solution reveals the presence of an aluminum-bound methyl group instead of ketone methyl, indicating no ROP reaction occurs during these NMR acquisitions.…”
Section: Rop Catalysismentioning
confidence: 62%
See 1 more Smart Citation
“…12 etc. In the presence of one equiv of e-CL, the 27 Al chemical shift of 2b moves upfield to 129 ppm (Dv 1/2 = 11157 Hz), consistent with an increase in coordination number for a neutral organo-aluminum complex. 75,80 The 1 H NMR spectrum of the same solution reveals the presence of an aluminum-bound methyl group instead of ketone methyl, indicating no ROP reaction occurs during these NMR acquisitions.…”
Section: Rop Catalysismentioning
confidence: 62%
“…75,80 The 1 H NMR spectrum of the same solution reveals the presence of an aluminum-bound methyl group instead of ketone methyl, indicating no ROP reaction occurs during these NMR acquisitions. The upfield change of the observed 27 Al chemical shift of 2b upon addition of e-CL is thus ascribable to the coordination of the heterocyclic monomer to aluminum, presumably via carbonyl oxygen atom. This hypothesis is consistent with the X-ray structure of an aluminum e-CL complex supported by a biphenolate ligand as elucidated by Lewi½ski et al 81 On the basis of the fact that the ROP rates of 2a-c are governed by the N-substituents, we propose that the monomer coordination proceeds predominantly, though perhaps not exclusively, on the two X-N-O (X = C for 2a-c or X = alkoxide for propagating intermediates) faces of the pseudo-tetrahedral catalysts.…”
Section: Rop Catalysismentioning
confidence: 90%
“…These complexes are intriguing as their catalytic activities are finely tunable by judiciously varying the peripheral substituents on the two phenolate rings and/or the bridge in between. While most studies concentrate on metal complexes of tetradentate biphenolate ligands such as ONNO (Ovitt and Coates, 2000; Zhong et al, 2002; Hormnirun et al, 2006; Zelikoff et al, 2009; Chen et al, 2012; Gao et al, 2015; Jones et al, 2015; Kirk et al, 2016; MacDonald et al, 2016; McKeown et al, 2016; Robert et al, 2017; Pang et al, 2018), OSSO (Buffet and Okuda, 2011; Buffet et al, 2011), ONSO (Stopper et al, 2012), and ONOX (X = OR, NR 2 ) (Alcazar-Roman et al, 2003; Gendler et al, 2006; Tang and Gibson, 2007; Phomphrai et al, 2010; Wichmann et al, 2012) as exemplified in Figure 1, parallel research centered upon tridentate counterparts is relatively rare (Chmura et al, 2006; Chang and Liang, 2007; Hsu and Liang, 2010; Liang et al, 2011, 2013a,b,c,d,e; Huang et al, 2013; Klitzke et al, 2014a,b; Chang et al, 2016).…”
Section: Introductionmentioning
confidence: 98%
“…It has been documented that complexes of tridentate OOO (Huang et al, 2013), ONO ( 1a-c ) (Liang et al, 2013a,b,c,d,e), and OPO ( 2a-b ) (Chang and Liang, 2007; Hsu and Liang, 2010; Liang et al, 2011; Chang et al, 2016) are active catalyst precursors for ROP of ε-caprolactone (ε-CL) or lactides (LAs). Studies on complexes of 1 and 2 have revealed that substituents at the pnictogen donor have decisive impacts on ROP catalysis if living polymerization is the goal.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the non-cytotoxic property and strong Lewis acidity of titanium, Ti complexes 22,23,[30][31][32][33] are commonly used catalysts in LA ROP. Numerous Ti complexes bearing various ligands such as calix [4] arene, 33,34 Schiff base, [35][36][37][38][39] salen, [40][41][42] salan, [43][44][45][46] phenolate, [47][48][49][50] aminophenolate, 51,52 benzotriazole phenolate, [53][54][55] phosphinophenolate, 56 thiophenolate, 57,58 bis-phenolate-N-heterocyclic carbene, 45 pyridonate, 59,60 and pyrrolide 61 have been reported to exhibit considerable catalytic activity or controllability, which is contributed by ligands. However, for most studies, focusing on materials is inconvenient, because the synthesis and purication of Ti catalysts are time-consuming processes.…”
Section: Introductionmentioning
confidence: 99%